Prośba o pomoc w rozwiązaniu przykładu:

[tex](2)^{-15} *(\frac{1}{4} )^{-7} /(0,5)^{-3}[/tex]

Chcę sprawdzić, czy dobrze rozwiązałam.


Odpowiedź :

Odpowiedź:

[tex]\dfrac{2^{-15}\cdot(\frac{1}{4})^{-7}}{(0,5)^{-3}}=\dfrac{(\frac{1}{2})^{15}\cdot((\frac{1}{2})^2)^{-7}}{(\frac{1}{2})^{-3}}=\dfrac{(\frac{1}{2})^{15}\cdot(\frac{1}{2})^{-14}}{(\frac{1}{2})^{-3}}=\dfrac{(\frac{1}{2})^1}{(\frac{1}{2})^{-3}}=(\frac{1}{2})^{1-(-3)}=\\\\\\=(\frac{1}{2})^{1+3}=(\frac{1}{2})^4=\frac{1}{16}[/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

2^-15*(1/4)^-7/0,5^-3=

=2^-15*4^7/(1/2)^-3=

=2^-15*(2^2)^7/2^3=

=2^-15*2^14/2^3=

=2^-1/2^3=

=2^-4=

=(1/2)^4=1/16